PENGEMBANGAN MATERI AJAR TEKS BIOGRAFI BERBANTUAN WONDERSHARE FILMORA DI KELAS X SMA NEGERI 7 MEDAN - Sri Hartati Sinaga; Adisaputera , Abdurahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of developing teaching materials for biographical texts assisted by Wondershare Filmora in class X of SMA Negeri 7 Medan, producing teaching materials for biographical texts assisted by Wondershare Filmora, and determining the feasibility of the teaching materials produced. This study uses the Research and Deeplopment (R&D) method with the Borg and Gall model which consists of five stages, namely potential and problems, data collection, product design, design validation, and design revision. Data collection techniques in this study are interviews, questionnaires, and observations. Data analysis techniques in this study use a linkert scale to determine the feasibility of the teaching materials that have been developed. The development of teaching materials is carried out by adding pre-existing materials and adding examples of contemporary and relevant biographical texts to the lives of today's students so that learning becomes more interesting and easier to understand. The product developed is teaching materials for biographical texts assisted by video media using Wondershare Filmora. The results of the study showed that the developed teaching materials obtained a level of feasibility of